Fiscal stimulus in expectations-driven liquidity traps - Lustenhouwer, Joep (Discussion paper series, 2020)
I study liquidity traps in a model where agents have heterogeneous expectations and finite planning horizons. Backward-looking agents base their expectations on past observations, while forward-looking agents have fully rational expectations. Liquidity traps that are fully or partly driven by expectations can arise due to pessimism of backward-looking agents. Only when planning horizons are finite, these liquidity traps can be of longer duration without ending up in a deflationary spiral. I further find that fiscal stimulus in the form of an increase in government spending or a cut in consumption taxes can be very effective in mitigating the liquidity trap. A feedback mechanism of heterogeneous expectations causes fiscal multipliers to be the largest when the majority of agents is backward-looking but there also is a considerable fraction of agents that are forward-looking. Labor tax cuts are always deflationary and are not an effective tool in a liquidity trap.